Comparison of a Virtual and in-Person OSCE on Advanced Communication Skills: Qualitative Insights from Medical Student Debrief Transcripts - Alex Choi; Tanya D. Murtha; Laura J. Morrison; Jaideep S. Talwalkar (Journal of Medical Education and Curricular Development)
OBJECTIVES This study investigates the differences between in-person versus virtual format of an advanced communication skills OSCE through thematic analyses of post-OSCE debrief transcripts. METHODS Two cohorts of senior medical students participated in either a 2019 in-person or 2021 virtual advanced communication skills OSCE. Students were grouped in triads and rotated through three of five possible cases. Afterwards, students participated in a faculty-led debrief (in-person in 2019, virtual in 2021). Inductive thematic analysis was used to compare the themes and the ratio of comments related to the themes were compared between the virtual and in-person OSCEs. RESULTS Thematic analyses for both in-person and virtual OSCEs identified the same four major themes (Case Review, Emotional Response, Feedback, and Reflection) and 11 subthemes. However, the ratio of comments related to Case Review was lower in the virtual OSCE compared to in-person (P  < .0001). Analysis of subthemes within Case Review revealed the percentage of comments was higher for Content and lower for Challenges in the virtual OSCE compared to in-person (both P  < .0001). There were no differences in the ratios of comments related to Emotional Response, Feedback, and Reflection, or their subthemes. CONCLUSION A virtual advanced communications skills OSCE for medical students showed identical qualitative themes to that from a prior in-person OSCE. However, students in the virtual OSCE focused more on matter-of-fact discussions about case content and less about the challenges they experienced. The findings suggest that some medical students may struggle with experiential learning in the virtual format, and have difficulty accessing or practicing their reflective observation skills based on Kolb's learning theory. Differences may be attributable to the additional cognitive load in the virtual setting, inadequate structural safeguards, and/or other limitations of virtual communication.